Prevalence of antibiotic resistant enteric bacteria in the hands of street food vendors in Dhaka city - Hassan, Md Mahade; Chakrabarty, Ram Prosad; Siddique, Mohammad Anwar; Rahaman, Md Mizanur (Bangladesh Journal of Microbiology, 2018)
Foodborne pathogens are affecting public health globally. Street foods being an important part in daily life of urban people are considered as a major source of foodborne pathogens. The major sources of street food contamination are water and the unhygienic condition of the vendors and food preparing places. This study was carried out to assess the load of antibiotic resistant enteric bacteria in the hands of street food vendors. A total of 20 street food vendors were selected from various locations in the Dhaka University campus and their hands were rinsed with 500 mL normal saline. Most of the samples contained high total viable counts, total coliforms count and total fecal coliforms count. A total of 25 selective colonies were identified as enteric bacteria including E. coli, Klebsiella spp. and Acinetobacter spp. by biochemical tests and 16S rDNA sequencing. All these isolates showed high antibacterial resistance against Amoxacilin (64%) and most of them showed sensitivity against Ciprofloxacin (76%) and Azithromycin (72%). This study revealed that the hand hygiene of street vendors is very poor and may have serious implications for public health due to possible contamination of food. This study, therefore, suggests proper training and education of street food vendors in order to improve their knowledge of personal hygiene and sanitation. Bangladesh J Microbiol, Volume 34 Number 1 June 2017, pp 33-38